(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Methanol (MeOH) is widely used as a solvent for extracting bioactive compounds from plant materials, but its inherent toxicity may confound biological assays if not properly controlled. This study aimed to evaluate the developmental toxicity of MeOH in zebrafish embryos to determine the maximum concentration that can be safely used as a solvent without causing adverse developmental effects. Zebrafish embryos were exposed to a range of MeOH concentrations (0.39% to 24.98% v/v in embryo media). Survival rate, mortality, hatching rate, heartbeat rate, and teratogenic effects were assessed over 120 hours post-fertilization (hpf). Embryo survival decreased with increasing MeOH concentrations. The highest survival (91.7%) was observed at 0.39% MeOH, followed by 83.3% at 0.78%, and 50% at 1.56%. Concentrations ≥3.13% caused 100% mortality. The calculated LC50 was 1.58% MeOH. Hatching and heartbeat rates followed similar concentration-dependent trends. Teratogenic effects, including oedema, failure of tail detachment, and curved body, were observed at sub-lethal concentrations. Methanol exhibits significant developmental toxicity in zebrafish embryos at concentrations above 1.56%. This study establishes 1.56% MeOH as the maximum concentration tolerable without severe toxicity, providing a safe threshold for its use as a solvent in future bioassays involving plant extracts or other biological samples.